ANALISIS PENGELOLAAN PIUTANG PADA PT.WIRATIMUR SEGARA DI SAMARINDA - -, Kartika Aprilia (EKONOMIA, 2014)
This study was conducted to determine whether the management of accounts receivable that have been implemented in accordance with the internal control, the data used is primary data obtained from questionnaires to identify elements - elements of internal control. Questionnaires were used to be covered with a choice of